2021
DOI: 10.1063/5.0029847
|View full text |Cite
|
Sign up to set email alerts
|

Electron kinetics in standing and moving striations in argon gas

Abstract: The electron kinetics in moving and standing striations in direct current and radio-frequency discharges is studied. The discharge current is such that the thermalizing electron-electron collisions are negligible and the hydrodynamic description of electron component of plasma is not valid. Therefore, the onedimensional hybrid model is used which models the electrons using the Particle-in-Cell/Monte Carlo collisions method. It is obtained that the electron transport is non-local in space. The electron energy d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The growth rate, wave number and angular frequency or phase velocity of the instability can be deduced from the results of the PIC-MCC simulation, and their variations with the reduced electric field šø 0 š‘ ā„ can be compared with those given by the linear analysis of the fluid model, eqs. ( 21) and (22). These comparisons are shown in Figure 14 and Figure 15 for the wavelength and growth rate respectively.…”
Section: G Comparison With the Pic-mcc Modelmentioning
confidence: 93%
See 1 more Smart Citation
“…The growth rate, wave number and angular frequency or phase velocity of the instability can be deduced from the results of the PIC-MCC simulation, and their variations with the reduced electric field šø 0 š‘ ā„ can be compared with those given by the linear analysis of the fluid model, eqs. ( 21) and (22). These comparisons are shown in Figure 14 and Figure 15 for the wavelength and growth rate respectively.…”
Section: G Comparison With the Pic-mcc Modelmentioning
confidence: 93%
“…[4][5][6] ). Recently, a self-consistent hybrid simulation of dc and rf positive column plasmas in argon was presented 22 under conditions where the effect of Coulomb collisions and stepwise ionization were negligible. The electric field was not imposed but rather obtained from Poisson's equation, electron transport was described kineticaly with a Monte Carlo simulation, and continuity and drift-diffusion equations were used for positive ions.…”
Section: Introductionmentioning
confidence: 99%
“…Omitting only the N 2 (A 3 Ī£) excitation, N-elastic and N-ionization reactions from the reaction scheme did not have any noticeable effect on the striations (not shown here). Previous studies [23,27] have demonstrated that excluding the loss term due to ambipolar diffusion to the wall fails to produce the positive column. In our case, both the ambipolar diffusion to the wall and the vibrational excitation reactions play key roles in forming the standing striation in molecular nitrogen gas.…”
Section: (B)) the Density Of Nmentioning
confidence: 95%
“…, where Ī› = R tube 2.4 is the transverse discharge length (R tube is the tube or discharge radius) [27,31] and…”
Section: Mathematical Model and Problem Geometrymentioning
confidence: 99%
See 1 more Smart Citation